A new species of Guatteria (Annonaceae) from the Andean mountain forest of Colombia - Villanueva-Tamayo, Boris; Parra-Lizcano, Nicolas; Rios-Cervera, Jorge Enrique (Phytotaxa, 2024)
Guatteria is a Neotropical genus comprising ca. 175 species, widely distributed in the forests of Central and South America. Guatteria sanjorgense is described, illustrated and compared with morphologically similar species. This new species was found in the San Jorge Botanical Garden, a regional conservation area located in the biodiverse Andean forests of the upper Magdalena basin, Colombia. This species is characterized by unusual short stipes of less than 14 mm long and 5–12 globose monocarps.